Multimedia-cartographic internet service of the cultural heritage on the Puszcza Bukowa area - Ostrowski, Błażej (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The main objective of this research was to design a multimedia website with a collection of thematic maps to show the values of cultural heritage sites in the “Puszcza Bukowa” Forest (Szczecin Landscape Park “Beech Forrest”) for public and expert users. In the research, the cartographic method was used together with User Centred Design, geo-information operations on BDOT10k data, and JavaScript programming using the Leaflet library. In addition to the chamber work, field research was carried out in several cartographic and geo-information applications to obtain materials for multimedia. The research process consisted of four stages: conceptual, preparatory, execution and publication of the completed service. The result of the research became a multimedia-cartographic web service, an indication that a properly designed and coded collection of spatial information can significantly affect the dissemination of cultural knowledge in protected areas.